Clinical and morphological characteristics of neuroendocrine tumors of female reproductive organs - T. Sh. Tagibova; S. O. Nikogosyan; O. A. Anurova; V. V. Kuznetsov; Z. N. Khizrieva (Опухоли женской репродуктивной системы, 2014)
The paper deals with the clinical and epidemiological features of human neuroendocrine tumors (NET) and those of female reproductive organsin particular. It presents current approaches to classifying these neoplasms in relation to their embryogenesis and biological properties. The clinical and morphological features of NET of female genital organs are described in detail. Microscopic and immunohistochemical criteriacharacterizing NET are also given.